Wiley CPAexcel exam review 2014 study guide. - Whittington, Ray, 1948- (John Wiley & Sons, 2014)
This study guide includes the information needed to prepare for the computerized CPA exam. It contains all current AICPA content requirements in accounting regulation and includes detailed outlines, study guidelines, and skill-building problems to help candidates identify, focus on, and master the specific topics that need the most work. It includes multiple-choice questions with solutions, and includes simulation-style problems. --